World war C : lessons from the COVID-19 pandemic and how to prepare for the next one - Gupta, Sanjay, 1969-; Loberg, Kristin (Simon & Schuster, 2021)
Drawing on his insider access to the drama's unfolding, including conversations with the world's top public health experts, the CNN chief medical correspondent and America's frontline COVID-19 health journalist shares what he's learned and how we can prepare for--or prevent--the next pandemic.